Quantitatively Mapping the Assembly Pattern of EpCAM on Cell Membranes with Peptide Probes - Jing, Yingying; Zhou, Lulu; Chen, Junling; Xu, Haijiao; Sun, Jiayin; Cai, Mingjun; Jiang, Junguang; Gao, Jing; Wang, Hongda (Analytical chemistry (Washington), 2020)
Epithelial cell adhesion molecule (EpCAM) is an important type I transmembrane protein that is overexpressed on the surfaces of most cancer cells and involved in various biological processes such as cell adhesion and cell signaling. Although it plays crucial roles in cell functions and tumorigenesis, questions concerning the detailed morphology, molecular stoichiometry, and the assembly mechanisms of EpCAM on cell membranes have not been fully elucidated. Here, we used direct stochastic optical reconstruction microscopy (dSTORM) and relied on fluorophore-conjugated peptides to quantitatively analyze the assembly pattern of EpCAM with single-molecule precision. EpCAM was found to organize heterogeneous clusters with different sizes, which contain different numbers of EpCAM molecules on MCF-7 cell membranes. Moreover, dual-color dSTORM imaging revealed a significant correlation between EpCAM and tetraspanin CD9, and part of the EpCAM clusters could be disrupted by knockdown of CD9, which indicated that EpCAM might localize in tetraspanin-enriched microdomains (TEMs) and function cooperatively with CD9 on cell membranes. In addition, the assembly of the membrane EpCAM was found to be limited by both cytoskeleton and glycosylation. Overall, our work clarified the clustered distribution of EpCAM and revealed the potential mechanisms of its clustering at the molecular level, promoting a deeper understanding of the nano-organization of membrane proteins.